Relationship Between Transformational Leadership and Employees' Creativity with Psychological Empowerment as Mediator - Ibrahim, Nurshahira; Ismail, Azman; Mat, Norazila; Erhan, Tugba (UI Scholars Hub, 2023)
Research Aims: This study examines the mediating effect of psychological empowerment on the relationship between transformational leadership and employee creativity in a financial organisation in Peninsular Malaysia. Design/Methodology/Approach: Quantitative methods were employed in this study. Two hundred questionnaires were distributed to employees of Islamic financial institutions in Malaysia. Of these, only 153 questionnaires were usable. Random sampling and partial least squares structural equation modelling (PLS-SEM) techniques were utilised in data analysis. Research Findings: The results of the analysis showed that psychological empowerment had an indirect effect on the impact of transformational leadership on employee creativity in the organisation under study. Theoretical Contribution/Originality: The result aligned with Spreitzer's (1995) concept of self-motivation through increasing self-esteem and modifying resilience, which promotes motivational behaviour in organisations. Managerial Implication in the South East Asian Context: Transformational leadership has been shown to be effective in addressing crises in organisational management. Leadership that applies this concept is able to sustain the organisation and its competitiveness over time, especially in Asia. Research Limitation & Implications: During the duration of this research, the data were collected only once. The sample for this study was obtained from a single organisation, and the only method used to collect data was a questionnaire. In times of globalisation and economic turmoil, practitioners can use the findings of this study to practice transformational leadership to sustain and support the vision and mission of an organisation.